Immunology and Homeopathy. 4. Clinical Studies—Part 2. Issue 4 (2006) - Bellavite, Paolo; Ortolani, Riccardo; Pontarollo, Francesco; Piasere, Valeria; Benato, Giovanni; Conforti, Anita
Abstract : The clinical studies on the effectiveness of homeopathy in respiratory allergy (18 randomized trials and 9 observational studies) are described. The literature of common immunologic disorders including also upper respiratory tract infections (URTI) and otorhinolaryngology (reported in part 1), is evaluated and discussed. Most of initial evidence-based research was addressed to the question of whether homeopathic high dilutions are placebos or possess specific effects, but this question has been often equivocal and is still a matter of debate. The evidence demonstrates that in some conditions homeopathy shows significant promise, e.g. Galphimia glauca (low dilutions/potencies) in allergic oculorhinitis, classical individualized homeopathy in otitis and possibly in asthma and allergic complaints, and a few low-potency homeopathic complexes in sinusitis and rhinoconjunctivitis. A general weakness of evidence derives from lack of independent confirmation of reported trials and from presence of conflicting results, as in case of homeopathic immunotherapy and of classical homeopathy for URTI. The suitable methods to evaluate homeopathy effectiveness, without altering the setting of cure, are also analyzed.